Pembuatan Sistem Informasi Poktan Mustika Berbasis Website Company Profile Untuk Promosi Pupuk Organik Kopidara - Eva Magdalena Silalahi (JURNAL ComunitÃ Servizio : Jurnal Terkait Kegiatan Pengabdian kepada Masyarakat, terkhusus bidang Teknologi, Kewirausahaan dan Sosial Kemasyarakatan, 2024)
Supported by Kramat Jati Village in East Jakarta, Poktan Mustika is a microenterprise that converts shallot skins into Kopidara organic fertiliser. The focus of Community Service (PKM) initiatives at the UKI Faculty of Engineering is Poktan Mustika. With sustained cooperation (MoU) between the UKI Faculty of Engineering and Kramat Jati Village, East Jakarta, this PKM activity seeks to develop a Poktan Mustika information system based on the company profile website in order to promote Kopidara organic fertiliser online. Through coordination with local sub-district officials, interviews, and field observations, the PKM method culminates in the development of the Poktan Mustika website and a memorandum of understanding for cooperation. The Poktan Mustika website is optimised with the keywords 'organic fertiliser' and 'farmer groups' and is incorporated with Google Maps, Poktan Mustika YouTube, and Kopidara fertiliser. The identified challenge pertained to the requirement for training initiatives and the implementation of digital technology for administrators of Mustika Poktan.